Quality of life quality of life and health conditions in the Quilombola Community of Pastinho, Municipality of Tanhaçu, State of Bahia (BA), Brazil (Research, Society and Development, 2025)
Brazil, marked by miscegenation and the legacy of slavery, presents deep social inequalities that still affect Black and quilombola communities, reflected in limited access to healthcare services and a high prevalence of diseases. This study aimed to analyze the quality of life of residents in the Pastinho quilombola community, located in Tanhaçu-BA and officially recognized in 2013 by the Fundação Cultural Palmares. The research, descriptive and quantitative in nature, was conducted between January and March 2025 through structured questionnaires addressing sociodemographic variables, housing conditions, health, nutrition, and work, applied to 69 of the 110 families in the community. Data were organized in spreadsheets and analyzed using the JASP software, with descriptive statistics and Pearson’s chi-square test, adopting a significance level of 5% (p